2017
DOI: 10.1016/s0140-6736(16)31723-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of MRI in the diagnosis of fetal brain abnormalities in utero (MERIDIAN): a multicentre, prospective cohort study

Abstract: National Institute for Health Research Health Technology Assessment programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
225
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(235 citation statements)
references
References 15 publications
5
225
0
5
Order By: Relevance
“…The reason for having more females present for MRI is likely due to the fact that clinicians knew about the safety of MRI and that women of child-bearing age had no radiation risk while taking MRI scans [6,12] . Consequently, more males were referred for CT scans in view of cost, availability and lesser degree of radiation safety concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for having more females present for MRI is likely due to the fact that clinicians knew about the safety of MRI and that women of child-bearing age had no radiation risk while taking MRI scans [6,12] . Consequently, more males were referred for CT scans in view of cost, availability and lesser degree of radiation safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the cost of MRI, its safety profile and the ability to provide accurate soft tissue details make it highly indispensable to medicine. A recent study by griffiths et al clearly demonstrated the extended clinical value of MRI in diagnosis of fetal brain abnormalities [6] .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated the diagnostic accuracy of prenatal ultrasound to be around 70% and to be increased to more than 90% by additional intrauterine MRI, already at 18 weeks of gestation. Since in one third of study patients the clinical management was changed after obtaining the MRI results, intrauterine MRI is recommended as soon as possible after ultrasonographic suspicion of fetal brain anomaly [14].…”
Section: Imagingmentioning
confidence: 99%
“…Este bajo rendimiento despuĂ©s de las 24 semanas, es atribuido a la osificaciĂłn del crĂĄneo y al descenso de la cabeza fetal hacia la pelvis de la madre. Al adicionar la RMF, la exactitud diagnĂłstica alcanza un 92% para fetos menores de 24 semanas y para los mayores alcanza hasta un 94% 4 .…”
unclassified
“…El 85% de los casos de ventriculomegalia estĂĄn asociados a otras alteraciones. Una de las ventajas de la RMF, es la posibilidad de realizar una evaluaciĂłn anatĂłmica fetal completa en busca de alteraciones relacionadas en otros sistemas [2][3][4][5] .…”
unclassified